Diagnosis of Chronic Intestinal Pseudo-obstruction and Megacystis by Sequencing the ACTG2 Gene. - Milunsky, Aubrey; Baldwin, Clinton; Zhang, Xiaoying; Primack, Daniel; Curnow, Adrian; Milunsky, Jeff (J Pediatr Gastroenterol Nutr, 2017)
OBJECTIVES: The diagnosis of chronic intestinal pseudo-obstruction has depended on clinical features, manometry, and imaging. This report aimed to determine the efficacy of sequencing the actin γ-2 (ACTG2) gene for diagnosis. In addition, the goal was to determine how often a mutation would be found in our randomly collected cohort of probands and those probands published previously. METHODS: Whole exome sequencing was performed in 4 probands with chronic intestinal pseudo-obstruction. Subsequently, only the ACTG2 gene was sequenced in another 24 probands (total 28). We analyzed published data of 83 probands and our 28 (total 111) and determined how many had pathogenic variants and the precise genotype. RESULTS: Whole exome and Sanger sequencing revealed a pathogenic variant in the ACTG2 gene in 4 out of 28 of our probands and in 45 out of 83 published probands (49/111 [44.1%]). Moreover, a mutational hotspot in the ACTG2 gene was recognized. Genetic heterogeneity is evident. CONCLUSIONS: Pooled gene sequencing results from 1 individual in each of 111 families enabled a precise diagnosis of an ACTG2 mutation in 49 (44%). The benefit to patients and families of early confirmation of a motility disorder not only helps avoid unnecessary intervention, but also enables institution of appropriate treatments and avoidance of secondary disorders such as malnutrition and poor growth. Knowledge of a pathogenic variant in a parent, with a 50% risk of recurrence, provides an opportunity for genetic counseling.
Keywords: Actins; Adult; Child; Child, Preschool; Chronic Disease; Duodenum; Female; Fetal Diseases; Genetic Markers; Genetic Testing; Humans; Infant; Infant, Newborn; Intestinal Pseudo-Obstruction; Male; Mutation; Sequence Analysis, DNA; Urinary Bladder; Whole Exome Sequencing